Sobre la traducción de la terminología en los textos filosóficos y sociopolíticos (francés-español) - Ortega Arjonilla, Emilio (Anales de Filología Francesa, 2010)
In this article we try to review the different strategies that can be applied to translate terminological and phraseological units and/or culturèmes containing ideological aspects that have to be present, in a certaint way, in the target text of the translation. To be able to classify those difficulties of translation of ideology we start with a theoretical reflection about two main concepts: ideology and culture. As a result of this theoretical reflection we propose a practical application to the translation of ideology and cultural elements in philosophical and sociopolitical texts (from French into Spanish) in three different contexts: thematic contexts, historical contexts and linguistic and cultural contexts. Finally, we finish this article offering a serie of strategies of translation that could be used in all of those contexts from a traductological point of view.